2012
DOI: 10.1016/j.celrep.2012.08.036
|View full text |Cite
|
Sign up to set email alerts
|

A Gradient of ATP Affinities Generates an Asymmetric Power Stroke Driving the Chaperonin TRIC/CCT Folding Cycle

Abstract: SUMMARY The eukaryotic chaperonin TRiC/CCT uses ATP cycling to fold many essential proteins that other chaperones cannot fold. This 1 MDa hetero-oligomer consists of two identical stacked rings assembled from eight paralogous subunits, each containing a conserved ATP-binding domain. Here, we report a dramatic asymmetry in the ATP utilization cycle of this ring-shaped chaperonin, despite its apparently symmetric architecture. Only four of the eight different subunits bind ATP at physiological concentrations. AT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
124
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(147 citation statements)
references
References 67 publications
(99 reference statements)
17
124
1
Order By: Relevance
“…It has recently been found that the different CCT subunits of TRiC bind ATP with different affinities (28). For the TRiC chaperonin to close, every subunit does not need to bind ATP, unlike the ATP-binding mechanism in GroEL/ES (2), where every GroEL subunit has to bind an ATP for closure.…”
mentioning
confidence: 99%
“…It has recently been found that the different CCT subunits of TRiC bind ATP with different affinities (28). For the TRiC chaperonin to close, every subunit does not need to bind ATP, unlike the ATP-binding mechanism in GroEL/ES (2), where every GroEL subunit has to bind an ATP for closure.…”
mentioning
confidence: 99%
“…closure (35,36,63,64). Thus, a flexibly attached folded domain, itself not interacting with TRiC (such as GFP in the actin fusions), might be excluded from the cavity, adopting a topology in which the extended linker traverses the central channel (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…A recent comparative XRC and cryo-EM study has revealed that functional transition of GroEL into a relaxed state is associated with breaking of two salt bridges and transient asymmetry of the apical domains (Fei et al, 2013). Asymmetries can be also revealed in the octameric rings of TRiC, an eukaryotic group II chaperonin; in its ATP-binding hierarchy; and even in its transition states (Cong et al, 2012;Reissmann et al, 2012).…”
Section: C Pentameric Ligand-gated and Mechanosensitive Channelsmentioning
confidence: 99%